1977
DOI: 10.1901/jeab.1977.27-515
|View full text |Cite
|
Sign up to set email alerts
|

An Operant Analysis of Human Altruistic Responding

Abstract: Human altruistic responding (called give responding), which delivered a reinforcer to someone other than the responder, was compared to responding where the responder was the recipient of the reinforcer (called earn responding). The same type of response (button pressing), the same reinforcer (a point representing a penny), and the same reinforcer contingency (a 40-response fixed-ratio schedule) were used for both give and earn responding. Since points representing pennies were used to reinforce give and earn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
3
0
3
Order By: Relevance
“…Demonstrating that the behavior of one person is a relevant part of the environment of another in experimental contexts allows the description of social behavior from a natural science perspective. Early examples of this attempt include studies on cooperation (Hake, Donaldson, & Hyten, 1983; Hake, Olvera, & Bell, 1975; Hake & Schmid, 1981; Hake & Vukelich, 1972, 1973; Hake, Vukelich, & Kaplan, 1973; Hake, Vukelich, & Olvera, 1975; Marwell & Schmitt, 1975; Schmid & Hake, 1983; Schmitt, 1976, 1984, 1987), competition (Buskist, Barry, Morgan, & Rossi, 1984; Buskist & Morgan, 1987; Dougherty & Cherek, 1994; Hake, Olvera, & Bell, 1975; Lindsley, 1966), empathy (Watanabe & Ono, 1986), and altruism (Weiner, 1977).…”
Section: Experimental Analysis Of Operant Behavior Social Behavior An...mentioning
confidence: 99%
“…Demonstrating that the behavior of one person is a relevant part of the environment of another in experimental contexts allows the description of social behavior from a natural science perspective. Early examples of this attempt include studies on cooperation (Hake, Donaldson, & Hyten, 1983; Hake, Olvera, & Bell, 1975; Hake & Schmid, 1981; Hake & Vukelich, 1972, 1973; Hake, Vukelich, & Kaplan, 1973; Hake, Vukelich, & Olvera, 1975; Marwell & Schmitt, 1975; Schmid & Hake, 1983; Schmitt, 1976, 1984, 1987), competition (Buskist, Barry, Morgan, & Rossi, 1984; Buskist & Morgan, 1987; Dougherty & Cherek, 1994; Hake, Olvera, & Bell, 1975; Lindsley, 1966), empathy (Watanabe & Ono, 1986), and altruism (Weiner, 1977).…”
Section: Experimental Analysis Of Operant Behavior Social Behavior An...mentioning
confidence: 99%
“…Dado que se observó que todos los participantes que no establecieron intercambios verbales de cualidad estratégica permanecieron respondiendo en la alternativa no compartida, pese a que dicha alternativa de respuesta otorgaba la mitad de las ganancias posibles en relación con las ganancias disponibles por responder en la alternativa compartida, puede decirse que la tesis económica que intenta explicar la conducta social dictada desde constructos teórico-experimentales como el Paradigma Operante del Análisis Experimental de la Conducta (e.g. Azrin & Lindsley, 1956;Glenn, 2004;Hake & Vukelich, 1972;Hursh & Roma, 2013;Lindsley, 1966;Okouchi, 2012;Skinner, 1962;Weiner, 1977;Yi & Rachlin, 2004) o la Teoría de Juegos (e.g. Bilbao & Fernández, 1999;Camerer, 2003;Gibbons, 1997;Osborne, 2004;Rostek, 2010;Shubik, 1982) y que puede resumirse para fines prácticos en un enunciado tal como las consecuencias y su posible maximización son suficientes para promover la conducta cooperativa, no ha sido apoyada por los datos recabados en este experimento.…”
Section: Discussionunclassified
“…El Paradigma Operante del Análisis Experimental de la Conducta y la Teoría de Juegos son ejemplos de perspectivas cuyos enunciados fundamentales para explicar la conducta cooperativa descansan en un principio económico-utilitario básico: el de las ganancias y su posible maximización (e.g. Azrin & Lindsley, 1956;Bilbao & Fernández, 1999;Camerer, 2003;Dugatkin, 1977;Glenn, 2004;Hake & Olvera, 1978;Hake & Vukelich, 1972;Hursh & Roma, 2013;Homans, 1961;Okouchi, 2012;Osborne, 2004;Rostek, 2010;Shubik, 1982;Skinner, 1953Skinner, , 1962Stephens & Anderson, 1997;Weiner, 1977;Weingarten & Mechner, 1966;Yi & Rachlin, 2004).…”
Section: Introductionunclassified
“…Similarly, Weiner (1977) demonstrated that sharing, the participant's willingness to "give" reinforcement to other experimental participants (thereby diminishing his or her own reinforcement), is actively created when the participant's own history of receiving sharing from others is manipulated appropriately. Weiner's work suggests that conditions arranged to evoke sharing at one point in time may have a lasting, useful effect.…”
Section: Positive Adult Repertoiresmentioning
confidence: 98%